The effects of gonadotropin-releasing hormone agonist on final adult height among girls with early and fast puberty - Tseng, Chin-Hui; Lee, Yann-Jinn; Huang, Chi-Yu; Wu, Yi-Lei; Wang, Lu-Ting; Lin, Chao-Hsu; Cheng, Bi-Wen; Lo, Fu-Sung; Chang, Yu-Jun; Ting, Wei-Hsin (Frontiers in Endocrinology, 2023)
This study aimed to explore the impact of gonadotropin-releasing hormone agonists (GnRHa) on final adult height (FAH) in girls with early and fast puberty. The treatment group included 109 patients who received 3.75 mg monthly for at least one year, whereas the control group consisted of 95 girls who received no treatment. The treatment group was significantly older at the time of inclusion (chronological age (CA1), treatment vs control, 8.7 vs. 8.4 years, P<0.001), had a more advanced bone age (BA) (BA1, 11.5 vs. 10.8 years, P<0.001), BA1-CA1 (2.7 vs. 2.2 years, P<0.001), and shorter predicted adult height. (PAH1) (153.3 vs. 157.1 cm, P = 0.005) that was significantly lower than their target height (Tht) (PAH1-Tht, -3.9 vs. -1.3 cm, P=0.039). The FAH of the GnRHa and the control group were similar (157.0 vs. 156.7 cm, P=0.357), and were not significantly different from their Tht (FAH vs. Tht in the GnRHa group, 157.0 vs.157.0 cm; control group, 156.7 vs. 157.0 cm). In the subgroup analysis, FAH was significantly higher after GnRHa treatment in those with PAH1 less than 153 cm and Tht (154.0 vs. 152.0 cm, P=0.041), and those whose CA1 was between 8 and 9 years (158.0 vs 155.4 cm, P=0.004). We defined satisfactory FAH outcome as FAH-PAH1≧5 cm and significant factors were GnRHa therapy, PAH1 shorter than their Tht, age younger than 9 years, and faster growth velocity during the first year. GnRHa is effective in restoring the Tht in some early and fast pubertal girls, especially in those with poorly predicted adult height (PAH lower than 153 cm and shorter than their target height). A younger age at initiation of treatment and a faster growth velocity during treatment are associated with a better height gain.